“Turn-On” Fluorescent Assay of Biothiols Based on Nitrogen-Rich Polymer Carbon Nanostrips and Its Application in Cell Imaging - Xiangying Meng; Jinjuan Qiao; Ronglan Zhao; Hairong Chu; Ying Wang; Xiangyu Chen; Zhengjun Yi (Journal of Chemistry)
In this work, a sensitive and selective turn-on fluorimetric method has been developed for the determination of biothiols based on blocking Ag+-induced fluorescence quenching of nitrogen-rich polymer carbon nanostrips (NRPCNSs). Ag+ ion can induce the fluorescence quenching of NRPCNSs due to the formation of nonfluorescent coordination complexes via robust Ag-N interaction. Once addition of biothiols, such as cysteine (Cys) and glutathione (GSH), Ag+ ions prefer to interact with biothiols rather than NRPCNSs, which could be attribute to the formation of Ag-S bond, thus leading to effective fluorescent recovery of NRPCNSs. Under the optimized conditions, excellent linear relationships existed between the recovery degree of the NRPCNSs and the concentrations of Cys and GSH in the range of 0.05 μM to 10 μM and 0.2 μM to 30 μM, respectively. And, the limits of detection (LODs) for Cys and GSH are 16.5 nM and 65.1 nM, respectively. The detection system also shows high selectivity against other non-thiol amino acids. Moreover, the potential in practical applications of this proposed method has been demonstrated by detecting biothiols in human serum and fluorescence imaging of biothiols in living cells.